(untitled) (Proceedings of the International Conference on Education, 2021)
Telemedicine has reemerged as the way to provide patient care amid the COVID-19 pandemic. It poses a safe and cost-efficient alternative to presence-based health appointments. Integrating remote patient care into healthcare training during their pre-clerkship curriculum is crucial for them to acquire professional skills to succeed in their postgraduate practices. One technique to achieve this is role-playing. It provides a learning environment for students to experience their future professional context in a safe, controlled setting. An educational innovation was implemented in the Preclinical Skills course to train students to carry out a teleconsult using peer role-play simulation. The study considered a mixed approach with a cross-sectional and descriptive design. The sample consisted of 75 students in the third semester on a health undergraduate program at Tecnologico de Monterrey organized in teams; each member represented a different role: health professional, patient, and observer-evaluator. Three clinical cases (abdominal pain, bad breath, and insomnia) randomly assigned. Each one with a script containing the patient’s background, present illness with medical history. Students had to simulate a teleconsult according to their role, and the observer had to score a classmate’s performance. To describe their experience, students completed an anonymous questionnaire. Our results showed that students identified key points that allow a teleconsult to successfully develop, even when not having the same role in the dynamic. They also recognized their opportunity areas and highlighted these tools as useful for obtaining skills that will help them excel in their professional practice even after the COVID-19 pandemic.